Sense of agency and everyday life: Children's perspective. (September 2016) - Hilppö, Jaakko; Lipponen, Lasse; Kumpulainen, Kristiina; Virlander, Marika
Abstract: This paper discusses a socio-culturally informed study on children's sense of agency regarding their everyday lives. The empirical data comprise of open-ended interview situations where four elementary school children (age 9–10) reflect on their everyday life with the help of photographs they had themselves taken. The results highlight variation in the children's accounts of their sense of agency. In all, the results provide a nuanced understanding of how the children's own aspirations, beliefs, and competencies, from their perspective, were related to engagement in different practices in their everyday life.